Who commits to the community? Person-community fit, place attachment, and participation in local Japanese communities. (March 2023) - Chishima, Yuta; Minoura, Yukihisa; Uchida, Yukiko; Fukushima, Shintaro; Takemura, Kosuke
Abstract: We hypothesize that person-environment fit between individual values (traditional vs. modern) and environmental characteristics (rural vs. urbanizing communities) promotes place attachment and participation, while previous studies have examined these factors separately. To investigate this hypothesis, we qualitatively and quantitatively analyzed one rural and one urbanizing community under the same local government (Takizawa City) in Iwate Prefecture, a Northeastern region of Japan. In Study 1, qualitative data from brochures and interviews indicated that the rural community highly valued traditions, whereas the urbanizing community accepted changes in the community. In Study 2, we surveyed 1025 adults living in these communities and found that those who valued tradition showed higher place attachment and community participation in the rural (vs. the urbanizing) community, while those who valued modernization indicated higher place attachment in the urbanizing (vs. the rural) community. Different mechanisms of fostering individuals' commitment to the local community are discussed. Highlights: The effects of person-community fit on place attachment and community participation were examined. Qualitative data (Study 1) showed that the rural community valued traditions. Quantitative data (Study 2) revealed the effects of person-community fit. Residents' traditional values in the rural community were related to place attachment and participation. Residents' modern values in the urbanizing community were related to place attachment.